2020
DOI: 10.3390/cells9122629
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix Mechanical Properties and Regulation of the Intestinal Stem Cells: When Mechanics Control Fate

Abstract: Intestinal stem cells (ISC) are crucial players in colon epithelium physiology. The accurate control of their auto-renewal, proliferation and differentiation capacities provides a constant flow of regeneration, maintaining the epithelial intestinal barrier integrity. Under stress conditions, colon epithelium homeostasis in disrupted, evolving towards pathologies such as inflammatory bowel diseases or colorectal cancer. A specific environment, namely the ISC niche constituted by the surrounding mesenchymal stem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 141 publications
(173 reference statements)
1
24
0
Order By: Relevance
“…The intestinal mucosa is constantly subject to mechanical stimuli that can activate molecular signals on the epithelial cells and leads to alterations of the epithelium biology. Mainly two forms of mechanical forces act on the intestinal wall: contractile activities (i.e., peristalsis) and shear stress (due to the presence of food, gas, and fluids) (192,195,196). These forces heavily impact bowel morphogenesis.…”
Section: Extrinsic Regulation Of Ecm: Metabolic and Mechanical Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…The intestinal mucosa is constantly subject to mechanical stimuli that can activate molecular signals on the epithelial cells and leads to alterations of the epithelium biology. Mainly two forms of mechanical forces act on the intestinal wall: contractile activities (i.e., peristalsis) and shear stress (due to the presence of food, gas, and fluids) (192,195,196). These forces heavily impact bowel morphogenesis.…”
Section: Extrinsic Regulation Of Ecm: Metabolic and Mechanical Controlmentioning
confidence: 99%
“…An interesting study conducted on rat's small intestine revealed that ECM fibers are organized as two interwoven arrays running diagonally around the crypt wall: one set clockwise and the other one set counterclockwise and oriented at a range of angle ± 30-50 • (192,(195)(196)(197). This spatial arrangement provides mucosa with the right flexibility to fit stretch forces (192,(195)(196)(197). The ECM conveys this mechanical information to cells through an integrin network, activates focal adhesion kinase (FAK) and the extracellular signal-regulated kinase (ERK) signaling, finally leading to cell proliferation.…”
Section: Extrinsic Regulation Of Ecm: Metabolic and Mechanical Controlmentioning
confidence: 99%
“…As discussed, the matrix stiffness not only affects migration properties, cellular response to therapeutics, and cell fate [ 124 ] but also the phenotype of cancer cells. Decoupling matrix stiffness cues from other characteristics in cancer studies can be achieved utilizing engineered hydrogels, but we need to overcome technical issues in conventional mechanical characterization techniques, particularly at the length scale of individual cells.…”
Section: Scaffold-free 3d Modelsmentioning
confidence: 99%
“…Interestingly, αSMA staining also positively correlates with CRC development [ 100 ], indicating a continuous increase in the activated-fibroblast population. Matrix stiffness has a prominent role in the control of the physiological behavior of stem cells [ 101 ]. Indeed, culturing mesenchymal stem cells on soft or stiff substrates, it has been shown that stiffness by itself can drive the differentiation toward peculiar lineages and promotes cells proliferation [ 102 , 103 , 104 , 105 ].…”
Section: From Sustained Inflammation To Tumorigenesismentioning
confidence: 99%